Collection of letters regarding aid provided in making of movie "HiLo Country". (1997)
The AJM Library aided the production company with copies of tapes with local accents, etc.
Letters between Thayla Wright and Susan Hegarty about the Hi Low Country Film and 2 receipts and a letter to Thayla Wright From Tom Moore.
Master list item #46
File location is in the Raton File Cabinet drawer 3
Keywords: Arthur Johnson Memorial Library -- Raton, New Mexico; Letters -- Raton, New Mexico; Wright, Thayla -- Librarian -- Raton, New Mexico; Hegarty, Susan -- Speech and Dialects -- Los Angeles, California; Hi - Low Country Films